2000
DOI: 10.1159/000029466
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids May Reduce Neutrophilic Inflammation in Patients with Stable Chronic Obstructive Pulmonary Disease

Abstract: Background: Although both inhaled and oral corticosteroids have anti-inflammatory effects causing improvement in clinical symptoms and spirometry in the treatment of asthma, the role of corticosteroids in the management of chronic obstructive pulmonary disease (COPD) is controversial. Objective: To evaluate the effects of inhaled corticosteroids on sputum neutrophilia in clinically stable COPD patients. Methods: In total, 18 patients were enrolled in the study. During 2 months, 9 patients in group A inhaled fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 27 publications
0
32
0
2
Order By: Relevance
“…Conversely, there are no reports of excess pneumonia AEs with ICS use in randomised clinical trials in asthmatics. Although corticosteroids are felt to be less effective in modulating neutrophil function compared with other effector cells, such as eosinophils or mast cells [28], several reports suggest that ICScontaining regimens may reduce sputum neutrophilia in patients with COPD [29,30], perhaps by decreasing neutrophil chemotaxis [31]. However, there is some evidence that SAL may alter neutrophil function either through decreased adhesion to airway epithelium [32] or capillary endothelium [33] or by inhibiting respiratory burst activity [34]; yet an increase in the pneumonia signal was not observed with SAL therapy in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there are no reports of excess pneumonia AEs with ICS use in randomised clinical trials in asthmatics. Although corticosteroids are felt to be less effective in modulating neutrophil function compared with other effector cells, such as eosinophils or mast cells [28], several reports suggest that ICScontaining regimens may reduce sputum neutrophilia in patients with COPD [29,30], perhaps by decreasing neutrophil chemotaxis [31]. However, there is some evidence that SAL may alter neutrophil function either through decreased adhesion to airway epithelium [32] or capillary endothelium [33] or by inhibiting respiratory burst activity [34]; yet an increase in the pneumonia signal was not observed with SAL therapy in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these observations remain largely unknown. Although corticosteroids are less effective at neutralising COPDrelated airway inflammation than that occurring in asthma, several [25][26][27], but not all [28,29], studies have demonstrated that therapy with moderate-to-high doses of inhaled corticosteroids for several weeks can significantly attenuate some of the components of airway inflammation in COPD. Inhaled corticosteroids may also attenuate airway hyperresponsiveness [11], a known risk factor for morbidity and mortality in COPD [30].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed eNO to be elevated in current smokers with COPD when compared with otherwise healthy smokers, while EBC NOx has been described as being the same as in healthy smokers or increased when compared with healthy non-smokers [11]. COPD-associated airway inflammation may be affected by multiple factors, including cigarette smoking and GCS treatment [12, 13]. …”
Section: Introductionmentioning
confidence: 99%